Objeto de aprendizagem hiperligado com materiais manipuláveis para o ensino de geometria espacial para alunos com baixa visão na educação básica - Mendes Júnior, Josino Lucindo (2016)
This work had the objective to develop assistive technology (learning object) which enabled teaching and learning of spatial geometry by student with partial sight deficiencies, from observations made at the Centro de Apoio Pedagógico (CAP) do Centro Brasileiro de Reabilitação e Apoio ao Deficiente Visual (Cebrav). The Centro Integrado de Aprendizagem em Rede (Ciar) gave support for the achievement of the purposes of this work. The application was developed under discussions and meetings with the researcher, her advisor and the Ciar team, from the information collected at Cebrav and the requirements presented by the teacher and the students, subjects to this investigation. The research was to understand the object characteristics that must contain an associated learning object to manipulable material for the teaching of spatial geometry content for students with partial sight deficiencies. This investigation studied which characteristics a learning object hyperlinked to manipulable material for teaching spatial geometry content must have, to assist students with partial sight deficiencies in the context of a social-historical methodology purpose. The following objectives were defined: A) Analyze the characteristics of a learning object hyperlinked to manipulable material for students with partial sight deficiencies, with the teacher and the students collaboration; B) Identify the mediations conducted by a professor of mathematics and the strategies presented by students with partial sight deficiencies in math workshops, with the learning object Edrons aid, hyperlinked to manipulable material for teaching spatial geometry.The investigative approach was qualitative and the method adopted was the Pedagogical-Investigative Intervention (Intervenção pedagógico-investigativa). To do the research, the utilized instruments were the participants observation, the applying of questionnaires, video recordings, semi-structure interviews and the workshop activities. The theoretical assumptions that guided this study were based on the socio- historical conception of Vygotsky and the laws, decrees and resolutions from the Brazilian and International Legislation. The results show: A) The learning object Edrons is an assistive technology that provides resource and methodology for spatial geometry teaching/learning for students with partial sight deficiencies; B) Even in situations considered best for the use of assistive technology conducting pilot tests to students with partial sight deficiencies, situations of interference in the teaching/learning procedure can occur, in this case, the teaching mediation role is fundamental to potentiate the resolution of activities that use this technology; C) The teacher-researcher mediation with the use of manipulable materials allowed the students with partial sight deficiencies to develop manipulation and tactile exploration strategies of the objects, this potentiated their perception as to the relative positions between straight lines in space in written activities or virtual environment and also induced and potentiated the generalization of Euler's relation to students with partial sight deficiency. As an educational product of this research, we developed an application containing prism and pyramid activities for students with partial sight deficiencies.